Individual innovativeness as a mediating factor between selected communication factors and career advancement in a Malaysian Islamic higher learning institution - Ilfandy, Ayub; Wok, Saodah (University of Padjajaran, 2014)
Innovation has been identified as a crucial drive that determines the survival, growth and sustainability of many modern organizations. In today's competitive environment, innovation can be critical in driving both individual and organizational successes. More importantly, individual within the organizations are the key player in the implementation of innovativeness at work. Hence, this study investigates the mediating effect of innovativeness on the selected communication factors towards career advancement. Specifically, this study takes a close look on how communication efficacy, communication climate, mentoring, and networking influence academicians' innovative working behavior. These communication factors are believed to provide opportunities for the innovation and implementation of novel ideas that will aid employees in achieving their career goals, and thus become a platform for their career advancement in the organizations. This study adopted quantitative survey research design. Self-administered questionnaires were distributed to 70 lecturers at the International Islamic University Malaysia (IIUM). The findings indicate that there are significant and positive relationships found between all four communication factors with individual innovativeness. The results also indicate innovativeness is strongly correlated with career advancement. More importantly, the study found the mediating effect of innovativeness on communication factors towards career advancement, especially networking. Additionally, regression analysis found that networking is the best predictor for academicians' innovative working behavior.